Novel approach for SVPWM of two-level inverter fed induction motor drive - Olwi A. Elkholi; Mohamed A. Enany; Ahmed F. Abdo; Mahmoud Eid (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Due to their better DC bus utilization and easier digital realization, Space Vector Pulse Width Modulation (SVPWM) scheme is the most widely used PWM scheme. Also two level inverter is the traditional frequency converter because it has fewer components and is lower complex to control, but on the other hand it generates higher harmonic distortion. This paper presents the realization of novel SVPWM approaches applied to the three phase induction motor drives. Specifically various schemes are based on using more combinations of step operation in each cycle to approximate the reference vector, such as 24 and 48 step operations in each cycle. The basic principle of conventional SVPWM with different modulation index M is presented. The switching sequences of new approaches are described. The modulation signals waveforms, DC bus voltage utilization, De-rated motor torque, standard error of average torque, voltage and current harmonic of new approaches are analyzed by the MATLAB/SIMULINK software. The results confirms that 48 step SVPWM approach is the best compared to other approaches.